Homicide clearance: Discretionary and non-discretionary factors - Aziani, Alberto (European journal of criminology, 2023)
Previous studies have produced mixed findings regarding discretionary and non-discretionary factors associated with the likelihood of homicides being cleared. Performing Pearson?s ?2 test, logistic regressions, and random forest analyses on all homicide cases that occurred in Italy in 2014, we assess if factors pertaining to the discretionary domain ? that is, nationality, age, sex, socioeconomic status of the victim, previous convictions ? and non-discretionary factors ? for example, weapon, location, circumstance ? are correlated with the outcome of the investigation. The empirical analysis does not identify relations between victims? nationality, socioeconomic status, previous criminal records and homicide clearance. On the other hand, homicides whose victim is male are less likely to be cleared. While high media coverage correlates with a higher clearance rate, low media coverage is not correlated with the homicide case remaining unsolved. Finally, especially in Southern Italy where mafia organizations are more entrenched, homicides committed in a criminal environment have a lower chance of being cleared. With respect to Italy, the results indicate a lack of support for the discretionary perspective that argues? that police may use discretion in clearing homicide cases according to the sociodemographic characteristics of victims.